Global, regional and country-level 90-90-90 estimates for 2018: assessing progress towards the 2020 target. - Marsh,K; Eaton,JW; Mahy,M; Sabin,K; Autenrieth,C; Wanyeki,I; Daher,J; Ghys,PD (AIDS, 2019)
BACKGROUND: In 2014, the Joint United Nations Programme on HIV/AIDS (UNAIDS) and partners set the 90-90-90 target for the year 2020: diagnose 90% of all people living with HIV (PLHIV); treat 90% of people who know their status; and suppress the virus in 90% of people on treatment. In 2015, countries began reporting to UNAIDS on progress against 90-90-90 using standard definitions and methods. METHODS: We used data submitted to UNAIDS from 170 countries to assess country-specific progress towards 90-90-90 through 2018. To assess global and regional progress, overall and by sex for adults 15 years and older, we combined country-reported data with estimates generated with a Bayesian hierarchical model. RESULTS: A total of 60 countries reported on all three 90s in 2018, up from 23 in 2015. Among all PLHIV worldwide, 79% (67-92%) knew their HIV status. Of these, 78% (69-82%) were accessing treatment and 86% (72-92%) of people accessing treatment had suppressed viral loads. Of the 37.9 million (32.7-44.0 million) PLHIV worldwide, 53% (43-63%) had suppressed viral loads. The gap to fully achieving 73% of PLHIV with suppressed viral load was 7.7 million; 15 countries had already achieved this target by 2018. CONCLUSION: Increased data availability has led to improved measures of country and global progress towards the 90-90-90 target. Although gains in access to testing and treatment continue, many countries and regions are unlikely to reach 90-90-90 by 2020.